2009
DOI: 10.1111/j.1530-0277.2009.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine Response in the Nucleus Accumbens Core–Shell Border Differs From That in the Core and Shell During Operant Ethanol Self‐Administration

Abstract: Background Ethanol self-administration has been shown to increase dopamine in the nucleus accumbens; however, dopamine levels in the accumbal subregions (core, shell, and core-shell border) have not yet been measured separately in this paradigm. The present study was designed to determine if dopamine responses during operant ethanol self-administration are similar in the core, core-shell border and shell, particularly during transfer from the home cage to the operant chamber and during consumption of the drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 43 publications
3
51
4
Order By: Relevance
“…3;Bhatt et al, 2009;Villalba and Smith, 2013). Although direct and indirect striatal projections from nucleus accumbens (NAc) MSNs do not segregate to the same degree as MSNs in the dorsal striatum (Smith et al, 2013), to the extent that our findings in dorsal striatum can be generalized to the NAc (Howard et al, 2009), reductions in D2 MSN plasticity may also disrupt behavioral processes involved in reward. Activation of D1 receptors is critical for psychostimulant self-administration (Xu et al, 2000;Caine et al, 2007;Karlsson et al, 2008), whereas stimulating D2 receptors blocks the behavioral effects of psychostimulants (Beyer and Steketee, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…3;Bhatt et al, 2009;Villalba and Smith, 2013). Although direct and indirect striatal projections from nucleus accumbens (NAc) MSNs do not segregate to the same degree as MSNs in the dorsal striatum (Smith et al, 2013), to the extent that our findings in dorsal striatum can be generalized to the NAc (Howard et al, 2009), reductions in D2 MSN plasticity may also disrupt behavioral processes involved in reward. Activation of D1 receptors is critical for psychostimulant self-administration (Xu et al, 2000;Caine et al, 2007;Karlsson et al, 2008), whereas stimulating D2 receptors blocks the behavioral effects of psychostimulants (Beyer and Steketee, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…In the NAc, reductions of 3α,5α-THP were isolated to the “shore” (core-shell border), as no changes in 3α,5α-THP were detected exclusively in the shell or core. This is an interesting finding since ethanol associated cues and operant self-administration of ethanol both increase dopamine release in the “shore” following operant training (Howard et al, 2009), but in the core or shell only ethanol associated cues increase dopamine release following operant training. It is important to note, however, that acute systemic ethanol administration increases dopamine release in the NAc core and shell (Imperato and Di Chiara, 1986; Yim et al, 2000) where ethanol did not alter 3α,5α-THP levels.…”
Section: Discussionmentioning
confidence: 99%
“…After a week of post-surgical recovery, animals are trained to lever press for 10% sucrose solution in a Med Associates operant chamber (MedAssociates, Inc., Vermont, USA) outfitted with a lickometer, retractable lever, and sipper tube (as previously described in Howard et al, 2009). 2 Software from MedAssociates is used to design all operant programs (MedAssociates, Inc., Vermont, USA).…”
Section: Operant Trainingmentioning
confidence: 99%
“…Using these conditions, we have found that there is an accumbal dopamine increase at the initiation of ethanol consumption, which decreases over the course of the drink and postdrink periods as the dialysate ethanol concentration increases. 2,3,8,9 These experiments, when combined with data from pharmacological studies, have allowed us to parse out the strictly pharmacological effects of ethanol and self-administration associated environmental cues on changes in neurotransmitter concentrations.…”
Section: Applications and Limitationsmentioning
confidence: 99%